2016
DOI: 10.1021/acs.est.5b03333
|View full text |Cite
|
Sign up to set email alerts
|

Marine Oil Biodegradation

Abstract: Crude oil has been part of the marine environment for millions of years, and microbes that use its rich source of energy and carbon are found in seawater, sediments, and shorelines from the tropics to the polar regions. Catastrophic oil spills stimulate these organisms to "bloom" in a reproducible fashion, and although oil does not provide bioavailable nitrogen, phosphorus or iron, there are enough of these nutrients in the sea that when dispersed oil droplets dilute to low concentrations these low levels are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
141
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(145 citation statements)
references
References 68 publications
(105 reference statements)
4
141
0
Order By: Relevance
“…In a recent paper, Hazen et al (2016) asserted that nutrient might select for different hydrocarbon-degrading organisms. Interestingly, different bacteria developed between surface and bottom water incubations.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent paper, Hazen et al (2016) asserted that nutrient might select for different hydrocarbon-degrading organisms. Interestingly, different bacteria developed between surface and bottom water incubations.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is important to evaluate the potential of indigenous microorganisms (both prokaryotes and eukaryotes) from different oceanic basins to degrade oil (Hazen et al, 2016). Microbes from all three domains of life can exploit certain compounds from the ∼600 1000 tons of oil that are annually released globally from (a) natural seeps on the seafloor, (b) delocalized runoff from human activities, and (c) oil spills (National Research Council (US) Committee on Oil in the Sea: Inputs, Fates, and Effects, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, an oil well leak in the Campos Basin, 120-km off the coast of Rio de Janeiro, caused 3,700 barrels of oil to be released into the ocean (ANP, 2012). Recent studies have demonstrated the common presence of oil-degrading bacteria in several different deep-sea oil basins (Prince, 2005; Jurelevicius et al, 2013; Hazen et al, 2016). However, most studies have focused on assessing the bacterial community structure in the North Atlantic, Gulf of Mexico, and Mediterranean Sea.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations